Patch Testing for Evaluation of Hypersensitivity to Implanted Metal Devices: A Perspective From the American Contact Dermatitis Society. Issue 5 (September 2016) - Schalock, Peter C.; Crawford, Glen; Nedorost, Susan; Scheinman, Pamela L.; Atwater, Amber Reck; Mowad, Christen; Brod, Bruce; Ehrlich, Alison; Watsky, Kalman L.; Sasseville, Denis; Silvestri, Dianne; Worobec, Sophie M.; et al.
Abstract : The American Contact Dermatitis Society recognizes the interest in the evaluation and management of metal hypersensitivity reactions. Given the paucity of robust evidence with which to guide our practices, we provide reasonable evidence and expert opinion–based guidelines for clinicians with regard to metal hypersensitivity reaction testing and patient management. Routine preoperative evaluation in individuals with no history of adverse cutaneous reactions to metals or history of previous implant-related adverse events is not necessary. Patients with a clear self-reported history of metal reactions should be evaluated by patch testing before device implant. Patch testing is only 1 element in the assessment of causation in those with postimplantation morbidity. Metal exposure from the implanted device can cause sensitization, but a positive metal test does not prove symptom causality. The decision to replace an implanted device must include an assessment of all clinical factors and a thorough risk-benefit analysis by the treating physician(s) and patient.